Fine-Mapping of a Wild Genomic Region Involved in Pod and Seed Size Reduction on Chromosome A07 in Peanut (Arachis hypogaea L.) - Alyr, Mounirou Hachim; Pallu, Justine; Sambou, Aissatou (MDPI (Multidisciplinary Digital Publishing Institute), 2020)
Fruit and seed size are important yield component traits that have been selected during crop domestication. In previous studies, Advanced Backcross Quantitative Trait Loci (AB-QTL) and Chromosome Segment Substitution Line (CSSL) populations were developed in peanut by crossing the cultivated variety Fleur11 and a synthetic wild allotetraploid (Arachis ipaensis × Arachis duranensis)4x. In the AB-QTL population, a major QTL for pod and seed size was detected in a ~5 Mb interval in the proximal region of chromosome A07. In the CSSL population, the line 12CS_091, which carries the QTL region and that produces smaller pods and seeds than Fleur11, was identified. In this study, we used a two-step strategy to fine-map the seed size QTL region on chromosome A07. We developed new SSR and SNP markers, as well as near-isogenic lines (NILs) in the target QTL region. We first located the QTL in ~1 Mb region between two SSR markers, thanks to the genotyping of a large F2 population of 2172 individuals and a single marker analysis approach. We then used nine new SNP markers evenly distributed in the refined QTL region to genotype 490 F3 plants derived from 88 F2, and we selected 10 NILs. The phenotyping of the NILs and marker/trait association allowed us to narrowing down the QTL region to a 168.37 kb chromosome segment, between the SNPs Aradu_A07_1148327 and Aradu_A07_1316694. This region contains 22 predicted genes. Among these genes, Aradu.DN3DB and Aradu.RLZ61, which encode a transcriptional regulator STERILE APETALA-like (SAP) and an F-box SNEEZY (SNE), respectively, were of particular interest. The function of these genes in regulating the variation of fruit and seed size is discussed. This study will contribute to a better knowledge of genes that have been targeted during peanut domestication.
Genes 2020, 11(12), 1402
Keywords: peanut; domestication; SSR; SNP; NILs; QTL fine-mapping; pod and seed size; candidate genes; AGRISAN; Université Cheikh Anta Diop; Sénégal